2016
DOI: 10.1093/imrn/rnw077
|View full text |Cite
|
Sign up to set email alerts
|

The Number of Subsets of Integers with Nok-Term Arithmetic Progression

Abstract: Addressing a question of Cameron and Erdős, we show that, for infinitely many values of n, the number of subsets of {1, 2, . . . , n} that do not contain a k-term arithmetic progression is at most 2 O(r k (n)) , where r k (n) is the maximum cardinality of a subset of {1, 2, . . . , n} without a k-term arithmetic progression. This bound is optimal up to a constant factor in the exponent. For all values of n, we prove a weaker bound, which is nevertheless sufficient to transfer the current best upper bound on r … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 45 publications
2
37
0
Order By: Relevance
“…Keeping this in mind, it seems hopeless to provide a general solution to the counting problem, as it seems crucial to know the order of magnitude of ex(n, H) in order to establish a sufficiently strong supersaturation result. However, Balogh, Liu, and Sharifzadeh [5] have recently managed to settle a question that has a similar flavor without knowing the corresponding extremal function. Specifically, they showed that for infinitely many n, there are 2 Θ(Γ k (n)) many subsets of [n] that do not contain an arithmetic progression of length k; here Γ k (n) is the largest cardinality of a subset of [n] without a k-term arithmetic progression.…”
Section: Discussionmentioning
confidence: 99%
“…Keeping this in mind, it seems hopeless to provide a general solution to the counting problem, as it seems crucial to know the order of magnitude of ex(n, H) in order to establish a sufficiently strong supersaturation result. However, Balogh, Liu, and Sharifzadeh [5] have recently managed to settle a question that has a similar flavor without knowing the corresponding extremal function. Specifically, they showed that for infinitely many n, there are 2 Θ(Γ k (n)) many subsets of [n] that do not contain an arithmetic progression of length k; here Γ k (n) is the largest cardinality of a subset of [n] without a k-term arithmetic progression.…”
Section: Discussionmentioning
confidence: 99%
“…This conjecture was disproved by Saxton and Thomason [82], who gave a construction of 2 (1+ε) √ n Sidon sets (for some ε > 0), and also used the hypergraph container method to reprove the following theorem, which was originally obtained in [59] using the graph container method. The second result we would like to state was proved by Balogh, Liu, and Sharifzadeh [10], and inspired the proof presented in Section 4. Let r k (n) be the largest size of a subset of {1, .…”
Section: List Colouringmentioning
confidence: 74%
“…and k ∈ {2, 3, 5}, since in these cases it is known that ex(n, K s,t ) = Θ(n 2−1/s ) and ex(n, C 2k ) = Θ(n 1+1/k ). Very recently, Ferber, McKinley, and Samotij [38], inspired by a similar result of Balogh, Liu, and Sharifzadeh [10] on sets of integers with no k-term arithmetic progression, found a very simple proof of the following much more general theorem. Note that Theorem 4.2 resolves Conjecture 4.1 for every H such that ex(n, H) = Θ(n α ) for some constant α.…”
Section: Counting H-free Graphsmentioning
confidence: 95%
See 1 more Smart Citation
“…We claim that both A 2 and A 3 are of small size, |A 2 ∪ A 3 | = n 2/3+o (1) . Thus the contribution of A 2 ∪ A 3 to the number of multiplicative 3-Sidon sets is negligible: n n 2/3+o(1) = 2 o(π(n)) .…”
Section: Upper Boundmentioning
confidence: 90%